Assessing the health hazards of low-dose ethylmercury: Neurochemical and behavioral impacts in neonatal mice through matrix metalloproteinase activation and brain-derived neurotrophic factor release - Min Heui Yoo; Tae-Youn Kim; Ho-Kyong Kim; Ji-Hyun Yoo; Byoung-Seok Lee; Jae-Young Koh (Ecotoxicology and Environmental Safety)
Ethylmercury (EtHg) primarily enters the body through contaminated fish and mercury-containing vaccines, raising concerns about its neurotoxic risks, particularly for infants and young children. Although its neurodevelopmental impact has been suggested, research remains inconclusive. Given that neurite outgrowth, matrix metalloproteinase (MMP) activity, and brain-derived neurotrophic factor (BDNF) expression play critical roles in brain development and synaptic plasticity, we hypothesized that EtHg exposure disrupts these processes, leading to behavioral abnormalities. To test this hypothesis, we utilized a neonatal mouse model, exposing mice to a specific dose of EtHg comparable to potential human exposure levels. The exact dosage and exposure conditions were carefully selected to reflect real-world exposure scenarios. Our findings revealed that EtHg exposure led to significant alterations in brain development, including increased brain size and cortical thickness. These structural changes were accompanied by notable impairments in social interactions and behavioral patterns. Further analysis indicated that these effects were likely mediated by increased microglial activation and elevated BDNF expression in the cerebral cortex. Overall, our study suggests that EtHg disrupts neurodevelopment by activating microglia, leading to physiological and morphological changes in the brain. These findings highlight the need for further research on EtHg neurotoxicity and its implications for vulnerable populations, particularly infants and young children.